Need to Change Women’s role in Politics: A step towards gender equity - Kakoli Das (International Journal of Advanced Science and Technology, 2020)
Role of Women in Indian politics needs a significant change to bring both men and women in the same status. Women constitute half of the population but still they are deprived of their rights and remain marginalized. Though the Indian constitution guarantees political equality to all, yet women do not have equal access to the public sphere as men. Men regard women to be a part of the private sphere. To change women’s role in politics, greater women’s participation from the grass root to the top level is very necessary and along with that the patriarchal mind-set of our society has to change. In elections women’s participation as voters and campaigners has increased but their representation is very low. Women have very negligible presence in the legislatures both in the national and state level. Their presence in the various political parties is also very low. The political party’s does not think women as their partners in decision-making. Women’s role in the sphere of decision making is very insignificant. To make women visible in the field of politics and break the patriarchal mind-set, the whole political scenario has to change and become gender neutral. Therefore, the paper will try to understand the need and importance for changing the role of women in Indian politics, so that women have a greater presence in the political arena like the men.